Summer performance analysis of coal-based CCHP with new configurations comparing with separate system. (15th January 2018) - Wei, Maolin; Yuan, Weixing; Fu, Lin; Zhang, Shigang; Zhao, Xiling
Abstract: Conventional coal-based CCHP system currently is believed to be less efficient than separate vapor compression cooling system in summer. In this paper, new configurations of CCHP system (N-CCHP) are proposed and studied which apply comprehensive methods to improve the system performance. In the N-CCHP, an absorption heat pump is applied in power plant to heat the primary water instead of a traditional heat exchanger. And, a small turbine is used to improve system performance with high bleeding steam pressure. In substation, the primary water is used to drive an absorption chiller and liquid desiccant equipment in series. The domestic water is also produced by the primary water after regeneration of liquid desiccant. Key influencing factors of the N-CCHP system have been fully discussed. In this way, a highly efficient N-CCHP system configuration is obtained and is analyzed to compare with the electricity driven vapor compression (VC) refrigeration system in summer. Results show that the N-CCHP is energy saving and own better performances when the primary water transmission distance is less than 60 km, or the COP of the vapor compression chiller is lower than 7. Highlights: A CCHP (N-CCHP) system is proposed and its performance in summer is studied. The N-CCHP uses an absorption heat pump in the plant to provide heat. The N-CCHP provides independent cooling and domestic water with primary heat. Key influencing factors of the N-CCHP are discussed through mathematic methods. The N-CCHP shows better performance comparing with compression cooling system.